Kemampuan Argumentasi Ilmiah Calon Guru IPA melalui Pendekatan MIKiR selama Pandemi Covid-19 - D Diniya; Aldeva Ilhami; Ira Mahartika; Niki Dian Permana P; Om Prakash (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
Since the Covid-19 pandemic, learning at the university or school level has implemented online learning. Even though the learning is conducted online, the teacher candidate's scientific argumentation skills must be trained. One way is through the MIKIR approach. The purpose of this research is analyzing the science pre-service teachers’ scientific argumentation skills by using MIKIR approach during pandemic covid-19. This type of research is a quasi-experimental study with a one-shot case study design. The research sample was 50 pre-service teachers. The instrument was an argumentation essay test based on the argumentation aspects according to Toulmin; claim, data, warrant and backing. The science pre-service teachers’ scientific argumentation skills will be analyzed through the one-sample T test assisted by the SPSS version 22 application. The results of this study is shown by the T score, 0.010> 0.05, is larger than a significance level. It means that MIKIR approach during pandemic covid-19 can practice significantly to the scientific argumentation skills of science pre-service teachers. Keywords: science pre-service teachers’ scientific argumentation skills, MIKIR approach, science learning during pandemic covid-19 ABSTRAK Sejak pandemi covid-19, pembelajaran baik di tingkat universitas atau sekolah menerapkan pembelajaran daring (online). Meskipun pembelajaran dilakukan secara daring, kemampuan argumentasi ilmiah calon guru IPA tetap harus dilatihkan. Salah satu caranya adalah melalui pendekatan MIKiR. Adapun tujuan penelitian ini adalah mengukur pengaruh pendekatan MIKiR dalam pembelajaran online terhadap kemampuan argumentasi ilmiah calon guru. Jenis penelitian ini adalah penelitian kuasi eksperimen dengan desain one-shot case study. Sampel penelitian adalah 50 calon guru IPA. Instrumen yang digunakan berupa tes argumentasi berupa soal esai berdasarkan aspek argumentasi menurut Toulmin; claim, data, warrant dan backing. Kemampuan argumentasi ilmiah calon guru IPA akan dideskripsikan dan dianalisis melalui uji T satu sampel berbantuan aplikasi SPSS versi 22. Hasil penelitian ditemukan skor uji T 0,010 > 0,05 yang artinya pendekatan MIKiR selama pandemi covid-19 dapat melatihkan kemampuan argumentasi calon guru IPA secara signifikan.Kata kunci: kemampuan argumentasi ilmiah calon guru IPA, metode MIKiR, pembelajaran IPA selama pandemic covid-19